(3GdCSS GdfXQjI hGdJWHjbGJ GdYedjIs - (3eMehO MSjf(B, (3GdhGOjs ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2008)
(3GdfbhO hGdQHG hGdHfhc ,GdYbhO aj Gdabg GdGSdGej ,YbO GdeVGQHI GdGSdGej ,GdhOGFY hGdGSJKeGQ aj GdHfhc GdGSdGejI ,Jehjd GdeVGQHI aj GdHfhc GdGSdGejI ,HjY GdeQGHMI aj GdHfhc GdGSdGejI ,GdeTGQcI aj GdHfhc GdGSdGejI ,COhGJ GdJehjd hGdGSJKeGQ GdGNQi aj GdeUGQa GdGSdGejI ,GdCYeGd hGdNOeGJ GdeUQajI GdGSdGejI GdGNQi ,bjGS hJhRjY GdQHM aj GdHfhc GdGSdGejIs
(3HdjhZQGajG(B: (3U(B.269-271s
Keywords: (3GdGbJUGO GdGSdGejs; (3GdGbJUGO eGdjs; (3GdHfhc GdGSdGejIs; (3Gdabg GdGSdGejs